Sustainability for 3D Printing - Sandhu, Kamalpreet; Singh, Sunpreet; Prakash, Chander; Subburaj, Karupppasamy; Ramakrishna, Seeram; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
With advancement in modern technology human life span in 21st century has significantly improved as compared to past centuries. Indeed, the manufacturing and household wastes have also boosted in the same era, presenting a hazardous condition to the various living beings. However, through smart methodologies, it can be possible to recycle/reuse of the different types of wastes as a feedstock convenient for specialized manufacturing technologies, such as 3D printing. This means that through proper facilities the waste can be used as the raw material for the printing technologies with characteristic at par with the virgin feedstock. Furthermore, producing the feedstock using waste materials will help to reduce the cost of the processing material, productivity and eco-friendliness of this manufacturing technology. This book will cover a boarder aspect of such efforts wherein various applications and state of art solutions will be discussed in a comprehensive way. This book will be much interest for academics, research and entrepreneur who are working in the field materials science, 3D printing, and manufacturing because of its coverage of state of art solution in the field of commercial, industrial and healthcare products.
Recent innovations and applications of 3D printing -- Concept of waste to wealth through 3D printing -- Technological aspects for waste treatment -- 3D Printing Materials -- Waste to feedstock: An example to the various hows?- Implication of recycled waste materials with 3D printer -- Sustainability and life cycle assessment -- Practical application and success stories.
Keywords: Industrial engineering; Production engineering; Environmental sciences -- Social aspects; Environmental management; Industrial and Production Engineering; Environmental Social Sciences; Environmental Management; Three-dimensional printing -- Environmental aspects; Remanufacturing